Tunneling of the femoral head with regenerative cryotherapy in children with Legg – Calve – Perthes disease - G. V. Slizovskiy; I. I. Kuzhelivskiy; L. A. Sitko; E. J. Anikina (Бюллетень сибирской медицины, 2017)
A subdestructive cooling of osteonecrosis of femoral head in children with Perthes disease (II) followed by activation of reparative processes in bone tissue was performed. It ensured the functional recovery of supporting limb capacity, reduced rehabilitation period by 23%, and improved the quality of patients’ life. Simultaneous biostimulating operation of tunneling and cryotherapy in management of necrotized femoral head is operation of choice for children with Perthes disease.